Effects of Neurolytic Concentrations of Alcohol and Phenol on Dacron and Gore–Tex Vascular Prosthetic Grafts. Issue 6 (November 1994) - Gale, David W.; Valley, Marc A.; Rogers, James N.; Poterack, Karl A.
Abstract : Background and Objectives: Neurolytic nerve block, using either alcohol (A) or phenol (P), is frequently used to treat intractable pain. However, these agents may disrupt the integrity of prosthetic vascular grafts. To investigate this possibility, the tensile strength of Dacron (Meadox Medicals, Oakland, NJ) and Gore–Tex (W. L. Gore Associates, Flagstaff, AZ) vascular grafts was determined after in vitro exposure to various clinically used concentrations of A or P. Methods: Segments of Dacron and Gore–Tex graft were placed in the following solutions: saline (S), 6% and 9% P, and 25%, 50%, 75%, and 100% A, and stored at 23° ± 1°C for 72 hours. Axial maximum load (in kilonewtons, KN) and strain (in mm/mm) were determined with an Instron universal testing machine (Instron Corporation, Camden, MA). Samples from the S, 9% P, and the 100% A groups were evaluated using a scanning electron microscope. Results: Dacron tensile strength decreased a maximum of 23% after exposure to 50%, 75%, and 100% A. Dacron strain capacity decreased after exposure to A (50%, 75%, 100%) and P (6%, 9%). Scanning electron microscope of both P and A showed significant degradation. No changes were found in the Gore–Tex group after exposure to P or A, however, scanning electron microscope of the 100% A sample showed moderate fiber degradation. Conclusions: The study shows that Dacron woven grafts are degraded by concentrations of A of at least 50%, and to a lesser extent, concentrations of at least 6%, while Gore–Tex had only minimal changes. While neurolytic block offers distinct advantages in patients with terminal cancer pain, the findings suggest that the use of more conservative modalities, such as oral medication regimens, be considered for the treatment of intractable pain in patients with vascular prosthetic grafts that are proximate to the proposed site of neurolysis.